The Causal Factors Affecting Income Inequality: A Case Study of Middle and Low Income Level Countries: ปัจจัยที่มีอิทธิพลต่อความเหลื่อมล้ำทางรายได้: กรณีศึกษากลุ่มประเทศรายได้ปานกลาง - Techaniyom, Kosin; Kittisaknawan, Chalermchai; Arakpothchong, Wutthichai; Pinit, Worapol (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ งานวิจัยชิ้นนี้ มีวัตถุประสงค์หลักเพื่อวิเคราะห์ปัจจัยที่ทำให้เกิดความเหลื่อมล้ำของรายได้ของประชาชนในกลุ่มประเทศรายได้ปานกลางของโลก โดยใช้ตัวชี้วัดความเหลื่อมล้ำด้านรายได้ Gini Coefficient หรือ ดัชนีสัมประสิทธิ์ความเหลื่อมล้ำเป็นตัวแทน ซึ่งรวบรวมข้อมูลทุติยภูมิจาก 101 ประเทศที่มีรายได้ปานกลางในระหว่างปี 2000–2017 และใช้วิธีการ Balanced Panel Data Analysis ในการวิเคราะห์ ที่ประกอบไปด้วยกลุ่มปัจจัยที่ใช้การทำนาย ได้แก่ 1) กลุ่มตัวแปรการเปิดประเทศจากโลกาภิวัตน์ใช้ตัวแปรเงินลงทุนโดยตรงจากต่างชาติคิดเป็นดอลลาร์สหรัฐ และตัวแปรสัดส่วนการส่งออกสินค้าและการบริการคิดเป็นสัดส่วนจากผลิตภัณฑ์มวลรวมประชาชาติเป็นตัวแทน 2) กลุ่มตัวแปรการเจริญเติบโตทางเศรษฐกิจซึ่งใช้ตัวแปรรายได้มวลรวมประชาชาติตามการคำนวณค่าเงินสากล และตัวแปรรายจ่ายของรัฐบาลสุดท้ายต่อผลิตภัณฑ์มวลรวมประชาชาติ 3) กลุ่มตัวแปรโครงสร้างทางระบบเศรษฐกิจซึ่งใช้ตัวแปรอัตราเงินเฟ้อจากดัชนีราคาผลิตภัณฑ์มวลรวม และตัวแปรสัดส่วนการว่างงานจากแรงงานทั้งหมดเป็นตัวแทน 4) กลุ่มตัวแปรโครงสร้างภูมิประชากรศาสตร์โดยใช้ตัวแปรจำนวนประชากรในเขตเมืองต่อประชากรทั้งหมด และตัวแปรการจ้างงานในภาคอุตสาหกรรมจากจำนวนแรงงานทั้งหมด เป็นตัวแทน 5) กลุ่มตัวแปรตัวแทนธรรมภิบาลของรัฐโดยใช้ ตัวแปรดัชนีความโปร่งใสและการเรียกร้องตามสิทธิ และ ตัวแปรดัชนีการควบคุมการทุจริตเป็นตัวแทน ผลการทดสอบพบว่าตัวแปรทุกตัวมีความนิ่งอยู่ในระดับ I (1) และมีความเหมาะสมในการทดสอบแบบจำลองด้วยวิธี Random Effect ซึ่งพบผลที่เป็นไปตามทฤษฎีกล่าวคือ สัดส่วนการว่างจากประชากรวัยแรงงาน (b = 0.437) และ รายได้มวลรวมประชาชาติตามการคำนวณค่าเงินสากล (b = 9.130) มีผลต่อดัชนีความเหลื่อมล้ำ Gini อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 นำไปสู่ผลสรุปสำคัญได้แก่ 1) ยิ่งประเทศร่ำรวยมากขึ้นจะยิ่งใช้จ่ายมากขึ้นแต่กลับทำให้ความเหลื่อมล้ำทางรายได้มากขึ้น ดังนั้น จึงควรเน้นการใช้จ่ายไปที่กลุ่มประชากรที่เป็นเป้าหมายมากกว่าการใช้จ่ายปริมาณมาก 2) การว่างงานเป็นปัจจัยที่มีผลต่อความเหลื่อมล้ำ รัฐควรมีแนวทางให้เกิดการจ้างงานมากที่สุด ABSTRACT The main objective of this research was to analyze factors which resulted in income inequality of the population in middle-income countries across the world by means of Gini coefficients. Secondary data from 101 middle-income countries between 2000 and 2017 was collected, and a balance panel data analysis was carried out based on five groups of predictive variables. The first group of variables was related to being open as a result of globalization–net foreign direct investment (BoP, current US) and the export of goods and services (% of GDP). The second group consisted of economic growth-related variables–GNI, PPP (current international ) and general government final consumption expenditure (% of GDP). The third group was economically-related variables–Inflation, GDP deflator: linked series (annual %) and total unemployment (% of total labor force). The fourth group consisted of demographic variables–urban population (% of total population) and employment in industry (% of total employment). The fifth group involved good governance-related variables– voice and accountability and the control of corruption. The results demonstrated that all these variables were stable at the level I (1), which was appropriate for the random effect method. They were in line with assumptions of this research. That is, the unemployment of the working-age population (b = 0.437) and the GNI, PPP (current international ) (b = 9.130) had influence on the Gini coefficient at the statistically significant level of .05. There were two conclusions that were supported by the findings of this research: 1) the wealthier the countries were, the higher their expenditure were and the worse their income inequality situations were–The recommendation for this is to place an emphasis on the target population rather than a huge amount of expenditure and 2) unemployment resulted in income inequality–It is recommended that the government should provide an approach to achieve the highest rate of employment.